2014
DOI: 10.1038/nature13714
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA polymerase II activation by histone acetylation in single living cells

Abstract: In eukaryotic cells, post-translational histone modifications have an important role in gene regulation. Starting with early work on histone acetylation, a variety of residue-specific modifications have now been linked to RNA polymerase II (RNAP2) activity, but it remains unclear if these markers are active regulators of transcription or just passive byproducts. This is because studies have traditionally relied on fixed cell populations, meaning temporal resolution is limited to minutes at best, and correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
293
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(308 citation statements)
references
References 44 publications
13
293
2
Order By: Relevance
“…Finally, promoter regions containing H2BK20ac were associated with cell-type-specific biological functions. In contrast, H3K27ac was present at all active promoter classes, regardless of cell-type specificity, which is consistent with the association of this histone mark with transcriptional elongation (Stasevich et al 2014). Overall, these results indicate a unique, and hitherto unexplored, contribution of H2BK20ac to cell-type specific gene regulation and cell-type-specific biological functions at distal and proximal cis-regulatory elements.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, promoter regions containing H2BK20ac were associated with cell-type-specific biological functions. In contrast, H3K27ac was present at all active promoter classes, regardless of cell-type specificity, which is consistent with the association of this histone mark with transcriptional elongation (Stasevich et al 2014). Overall, these results indicate a unique, and hitherto unexplored, contribution of H2BK20ac to cell-type specific gene regulation and cell-type-specific biological functions at distal and proximal cis-regulatory elements.…”
Section: Discussionsupporting
confidence: 67%
“…Histone acetylation also plays an important role in the regulation of RNA Polymerase II (RNAP II) activation by enhancing the search kinetics of transcriptional activators and, later, accelerating the transition of RNAP II from initiation to elongation. 9 For example, studies in living cells revealed that H3K27ac associated with active promoters and enhancers can modify downstream transcription kinetics by as much as 50%. 9 …”
Section: Role Of Epigenetics In Chromatin Machinerymentioning
confidence: 99%
“…9 For example, studies in living cells revealed that H3K27ac associated with active promoters and enhancers can modify downstream transcription kinetics by as much as 50%. 9 …”
Section: Role Of Epigenetics In Chromatin Machinerymentioning
confidence: 99%
“…Of note, the concentrations at which C646 biochemically inhibits tubulin polymerization are similar to concentrations that have been applied in cellular assays. 4,6,8 These studies suggest the electrophilic reactivity of C646 can have functional effects on protein activity.…”
mentioning
confidence: 99%
“…5 C646 can be used to inhibit the p300/CBP-dependent histone modification H3K27Ac, which has been used in imaging studies to establish a causal role for histone acetylation in transcription in living cells. 6 Furthermore, C646 can selectively induce cell death in leukemia cells containing the AML-ETO gene fusion, which encodes a transcription factor whose activity is dependent on p300/CBP KAT function. 7,8 Recently there has been an increased interest in understanding the mechanisms and liabilities of pan-assay interference compounds (commonly referred to as PAINS).…”
mentioning
confidence: 99%